2019
DOI: 10.1080/14742837.2019.1681957
|View full text |Cite
|
Sign up to set email alerts
|

Alliance building and eventful protests: comparing Spanish and Portuguese trajectories under the Great Recession

Abstract: Social movement research has shed light on the relationship between processes of alliance building and multiple factors related to political opportunities, framing, identities, networks and resource mobilization. However, less is known about the impact of eventful protests on coalition building dynamics. Drawing on a paired comparison between the Portuguese and Spanish cycles of protest under the Great Recession, we aim at accounting for social movement alliances over time. While these countries present parall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 52 publications
3
10
0
Order By: Relevance
“…Though there are many directions in which numbers from Table 3 could be explored, an obvious one is a historical contextualisation of protest mobilization waves from the period of the Great Recession 2008-2015. Studies have established the surge of mass mobilizations in this period in Spain and Portugal (Accornero and Pinto, 2015;Portos, 2016;Romanos, 2017;Flesher Fominaya, 2017;Della Porta et al, 2017;Portos and Carvalho, 2019), and our data reconfirm these findings. In Portugal the relative stability in protest numbers between 2000 and 2008 made way to a general strike mobilizing 3 million people in 2010 and a peak in protest numbers in 2012.…”
Section: Summary Description Of Datasupporting
confidence: 88%
“…Though there are many directions in which numbers from Table 3 could be explored, an obvious one is a historical contextualisation of protest mobilization waves from the period of the Great Recession 2008-2015. Studies have established the surge of mass mobilizations in this period in Spain and Portugal (Accornero and Pinto, 2015;Portos, 2016;Romanos, 2017;Flesher Fominaya, 2017;Della Porta et al, 2017;Portos and Carvalho, 2019), and our data reconfirm these findings. In Portugal the relative stability in protest numbers between 2000 and 2008 made way to a general strike mobilizing 3 million people in 2010 and a peak in protest numbers in 2012.…”
Section: Summary Description Of Datasupporting
confidence: 88%
“…In periods of crisis, it is important to study union strategies in relation to broad patterns of social contention rather than as isolated phenomena. Studies of the post-2008 cycle of contention in Southern Europe have shown how unions aligned with other social actors in organizing mass protests so their repertoire of contention expanded, rather than contracted (Accornero and Pinto, 2015; Portos and Carvalho, 2019). Organized labour makes its voice heard through collective bargaining, but workers also express their grievances by means of protests, demonstrations or petitions (Campos Lima and Artiles, 2018), or as Mathers et al (2018) argue, trade union deinstitutionalization has ‘opened up civil society as a terrain on which to remobilise trade unionism as a social movement’ (p. 14).…”
Section: Union Strategies During the Great Recession: The Post-social...mentioning
confidence: 99%
“…unceasing and sustained wave of contention until the end of 2013" (see also Portos and Carvalho 2019). As is well documented, the massive protest wave in Spain spilled over into electoral politics, giving rise to a new party, Podemos, and leading to a significant restructuring of Spanish politics (e.g., della Porta et al 2017b;Vidal and Sánchez-Vítores 2019).…”
Section: Introductionmentioning
confidence: 98%
“…Faced with a dire economic situation and increasing European pressure, the mainstream left in government -PS in Portugal and PSOE in Spainannounced severe austerity measures throughout 2009(e.g., Bremer and Vidal 2018. Consequently, the two countries saw union-organized protest against the measures early in the crisis (e.g., Accornero and Ramos Pinto 2015;della Porta et al 2017a;; Portos 2019). Both countries experienced a turning point in 2011 when further noninstitutional actors entered the scene: Geração à Rasca (Screwed Generation) in in Portugal and 15M (named after the first large-scale protests on May 15, 2011) in Spain.…”
Section: Introductionmentioning
confidence: 99%